The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1128/jvi.00190-18
|View full text |Cite
|
Sign up to set email alerts
|

The 135 Gene of Goatpox Virus Encodes an Inhibitor of NF-κB and Apoptosis and May Serve as an Improved Insertion Site To Generate Vectored Live Vaccine

Abstract: Goatpox virus (GTPV) is an important member of the genus of the Capripoxviruses have large and complex DNA genomes encoding many unknown proteins that may contribute to virulence. We identified that the open reading frame of GTPV is an early gene that encodes an ∼18-kDa protein that is nonessential for viral replication in cells. This protein functioned as an inhibitor of NF-κB activation and apoptosis and is similar to the N1L protein of vaccinia virus. In the natural host, sheep, deletion of the gene from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The use of a specifically modified capripoxvirus as a live‐attenuated vaccine has been proposed and demonstrated as feasible by inactivating the kelch‐like gene (SPPV_019) in SPPV‐SA (Balinsky et al, ). More recently, Zhang, Sun, Chen, and Bu () showed that deleting a putative NF‐kB inhibitor (GTPV_135) enhanced antibody responses to a GTPV‐encoded peste des petits ruminants hemagglutinin. A long‐term goal in such vaccine development programmes would be to gain a better understanding of factors affecting the host range of these viruses.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a specifically modified capripoxvirus as a live‐attenuated vaccine has been proposed and demonstrated as feasible by inactivating the kelch‐like gene (SPPV_019) in SPPV‐SA (Balinsky et al, ). More recently, Zhang, Sun, Chen, and Bu () showed that deleting a putative NF‐kB inhibitor (GTPV_135) enhanced antibody responses to a GTPV‐encoded peste des petits ruminants hemagglutinin. A long‐term goal in such vaccine development programmes would be to gain a better understanding of factors affecting the host range of these viruses.…”
Section: Introductionmentioning
confidence: 99%
“…This was the same observed by Zhuetal. (2013) and Zhang et al (2018). Finally, after adaptation of SPV isolates, and investigation of some characters including the growth curve and growth kinetics of these SPV isolate, further studies are recommended for SPV vaccine preparation, that not only used for giving protection to sheep, but also can be used to vaccinate cattle under stress factors against LSDV.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplicity of infection (MOI) is a critical factor that must be carefully determined as it influences the virus growth dynamic and virus yield (Genzel et al, 2006;Trabelsi et al, 2012;Trabelsi et al, 2014) succeeded to adapt SPV (RM65 strain) firstly on lamb kidney cells, then on Vero cells after nine passages with MOI of 0.005, yielded a higher virus titer when compared to that achieved at a MOI of 0.001. For determination of virus particles inside the culture, Zhang et al (2018) applied indirect immunofluorescence assay when infected Lamb Testis (LT) cells with AV41(a strain of GPV) or its recombinants at an MOI of 0.05. In our study, we aim to use the lowest MOI which provides the highest titer with the optimum virus harvestation time.…”
Section: Introductionmentioning
confidence: 99%
“…The use of poxviruses as vaccine vectors in recombinant vaccines presents many advantages such as the large size of the viral genome (140–300 kbp) which can contain up to 25,000 bases of foreign DNA, their thermal stability, and their replication in the cytoplasm of infected cells without integration into the host genome. Several recombinant capripoxvirus-vectored vaccines have been generated using genes of Rift Valley fever [ 137 , 138 ], peste des petits ruminants [ 139 , 140 , 141 , 142 ], rinderpest [ 143 ], bluetongue [ 144 , 145 ]), foot-and-mouth disease virus Mp1-2A polyprotein [ 146 ], EG95 antigens from Echinococcus granulosus [ 147 ], and OMP25 outer membrane protein from Brucella [ 148 ]. Developed recombinant capripox vaccines have not yet been used at a large scale in the field despite having the ability to differentiate them between infected and vaccinated animals (DIVA).…”
Section: Vaccination Against Capripoxvirusesmentioning
confidence: 99%